Analysis of the Brayton cycle coupled with a small fluoride salt-cooled high-temperature reactor - Liu, Xiuting; Huang, Yanping; Liu, Minyun; Min, Luyue; Zhang, Ting; Li, Xinyu; Zhuo, Wenbin (Frontiers in Energy Research, 2023)
Considering the environmental conditions and transportation conditions of remote areas, an inherently safe integrated energy conversion system featuring miniaturization, modularization, and high environmental adaptability is needed. The small fluoride salt-cooled high temperature reactor (FHR) coupled with the Brayton cycle is one of the promising designs. This paper compares the efficiency, exergy efficiency, and exergy loss of four different configurations of the supercritical carbon dioxide (S-CO2) Brayton cycle coupled with a new small fluoride salt-cooled high temperature reactor. The S-CO2 recompressor Brayton cycle has the best overall performance. Meanwhile, the effects of the cooling conditions on thermal efficiency and exergy efficiency of different cycle configurations are discussed. When the core outlet temperature is 700 ℃, the efficiency of the designed S-CO2 recompressor Brayton cycle is about 42 44% when the cycle minimum temperature is 32 40 ℃. In conclusion, the designed small FHR coupled with the Brayton cycle system offers interesting performances in power generation, mineral mining, industrial steam supply, molten salt energy storage, high temperature hydrogen production in remote areas.